Automation of the compliance matrix «Discipline – Competence» (by example of the educational masters program «Financial Intermediation») - Zhurakhovska, Liudmyla (Technology audit and production reserves (Online), 2021)
The object of this research is the automation of the compliance matrix «Disciplines – Competences», which are the links between the list of compulsory and elective disciplines of the educational program according to the curriculum and the set of competencies of the graduate required by the Standard of higher education. The development of the educational program includes a combination of disciplines with «Program Learning Outcomes», which is listed in the Standard. One of the most problematic places is time-consuming of the process of «drawing-up» the links from «General Competencies» (GC) and «Professional Competencies» (PC) of disciplines to «Program Learning Outcomes» (PO). This problem is considered on the basis of the Educational and Professional Program (OPP) «Financial Intermediation» Academic Degree «Master» specialty 072 «Finance, Banking and Insurance» in the field of science 07 «Management and Administration» of the Department of Banking of Kyiv National University of Trade and Economics (KNUTE, Ukraine). The research methods are to use the design of relationships between logical elements («entities») of the data model (Entity-Relationship Model). To develop a compliance matrix «Disciplines – Competences» in the paper the author proposed a software application based on Excel (hereinafter «Application»), which allows to automate the construction of such links. There is a significant reduction in the time-consuming of preparing educational programs by guarantors and support groups. This is due to the fact that the proposed application has a number of features of use, in particular automates the construction of matrices of correspondence «Discipline – Competence». The method of automation of the compliance matrix «Disciplines – Competences» proposed in the research was successfully tested by the author in the development of educational and professional programs of KNUTE, namely «Financial Intermediation», «Management of Banking Business» and «Financial Brokerage». Thus, the application is universal and can be used by guarantors and support groups to build Compliance Matrices of the educational programs of other specializations and specialties.